Customary law of Austric-speaking tribes - Bhowmick, P. K. (Delhi : Kalpaz Publications, 2002)
With reference to West Bengali, India.
Includes bibliographical references (p. [175]-178) and index.
Keywords: CUSTOMARY LAW -- INDIA